A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae - Santos-Silva, Antonio; Botero, Juan Pablo; Tirant, Stéphane Le (Zootaxa, 2018)
Four new Mexican species are described: Ironeus curoei from Guerrero state, Psyrassa garciai from Tamaulipas state, Psyrassa belangeri from Guerrero state (Elaphidiini, Cerambycinae); and Cirrhicera bankoi from Chiapas state (Hemilophini, Lamiinae). A new Hesperophanini genus, Makromastax, and a new combination, Makromastax mandibularis are proposed. The current key to the Mexican genera of Hesperophanini is updated to include the new genus. Haplidus nitidus Chemsak and Linsley, 1963 is proposed as synonyms of Haplidus mandibularis Chemsak and Linsley, 1963. The male of Eburia (E.) girouxae is illustrated by the first time and Anelaphus hirtus is redescribed and figured. The geographical distribution of 9 species is expanded, the type locality of Osmidus guttatus is corrected, and Neocompsa intrincata is excluded from the fauna of the United States of America.